Building Critical Awareness Through HIV and AIDS Management Policy at Subdistrict and Village Level - Rokhmah, Dewi; Khoirun, Khoirun (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
The number of PLWHA in Jember Regency has been increasing every year from 2004 to 2016 always, hence HIV/AIDS prevention must involve the community, not just relying on programs from the Department of Health or KPAD. Jember Regent’s policy on HIV/AIDS Management Team at Subdistrict and Village Level strategically involve all components of the society. Society’s participation was not limited to physical participation but extended to critical awareness. This is a descriptive analytic study about logical thinking on fostering critical awareness on HIV/AIDS through subdistrict and village HIV/AIDS team regulated by Jember’s Regent. Policy analysis was done through Triangle of Policy Analysis theory which includes: context, content, process and actors. The result showed that Jember Regent’s policy on HIV/AIDS prevention teams at subdistrict and village level was very effective to foster community’s critical awareness in HIV/AIDS preventive programs at Jember Regency.